Epidemiologia e fatores de riscos para acidentes ocupacionais com perfurocortante: estudo tipo caso-controle - Santos, Joana Darc dos (2005)
Background The prevention of needlestick injury in health-care personnel (HCP) have been considered as a public health issue. Objective To know the risk factors for needlestick injury with HCP in a Brazilian hospital. Methods This study was conducted in a tertiary care public university hospital in Uberlândia, southeast of Brazil. The data was collected by anamnesis, State-Trait Anxiety Inventory (STAI) and the Beck Depression Inventory (BDI). Results Seventy cases of needlestick injury with 69 HCPs were registered. The mean age was 38.5 years-old. For the control-case study, 13 were excluded. There was difference between anxiety in the cases and in the control-case (p=0.00011), with moderate anxiety more prevalent in the cases (p = 0.000061; odds ratio = 6.25). There were more HPCs with normal depression among the control group (79.6%) than in the cases group (46.3%) (p = 0.00083; odds ratio = 4.53) Conclusions These accidents occur mainly with female and with assistant nurse; the hands, mainly the fingers, are more affected; most occur with needles; in the departments that attend patients; the risk factors are: pain related to the job and, mainly, anxiety and depression.